1997
DOI: 10.1128/iai.65.1.227-235.1997
|View full text |Cite
|
Sign up to set email alerts
|

Development of antibody-secreting cells and antigen-specific T cells in cervical lymph nodes after intranasal immunization

Abstract: Intranasal (i.n.) immunization with bacterial protein antigens coupled to cholera toxin B subunit (CTB) effectively induces mucosal, especially salivary immunoglobulin A (IgA), and nonmucosal antibody responses in mice. To examine the regional distribution of antigen-specific B and T cells after i.n. immunization, antibody-secreting cells and antigen-responsive T cells in cervical lymph nodes (CLN) were compared with those found after intraoral or subcutaneous (in the neck) administration of the same antigen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 30 publications
(52 reference statements)
3
25
0
Order By: Relevance
“…immunized mice, but not that of unimmunized mice [12], indicating that B cell activation and IgA isotype switching may have occurred in NALT before cell emigration. Strong IgA ASC responses were also detected in the draining lymph nodes of NALT [16]. In this study, we showed that these responses in NALT were related at several time points to those in SG after i.n.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…immunized mice, but not that of unimmunized mice [12], indicating that B cell activation and IgA isotype switching may have occurred in NALT before cell emigration. Strong IgA ASC responses were also detected in the draining lymph nodes of NALT [16]. In this study, we showed that these responses in NALT were related at several time points to those in SG after i.n.…”
Section: Discussionsupporting
confidence: 52%
“…Further work has shown that memory T cells could reside in NALT and also in the draining cervical lymph nodes for at least several months [12,16]. Such long lasting immunity may be desirable to prevent colonization of the nasal cavities, for example with pneumococci [5].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have also been reported using AgI/II and purified CTB conjugated proteins. 45 Booster immunization did not further enhance splenic responses, which instead declined after three booster immunizations. This may have been a result of the development of regulatory cells that would suppress such responses to AgI/II 46 and may indicate the development of 'split' tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…boosting, a modest increase in AgI/II-specific proliferation was found in cells from the CLNs that drain the nasal mucosa, but not in the NALT or a remote lymph node such as the ILN. Thus, it appears that recall of mucosal memory responses depends upon a pool of memory cells that are not immediately available at the inductive sites but must be recruited from more central lymphoid organs such as the spleen or possibly the deeper CLNs as suggested by Wu et al 45,47 With respect to the properties of the antigen chosen for study, extensive experience has shown that AgI/II is a potent immunogen; 48 this may influence the ability of CT or CTB to serve as an adjuvant or as a coupled delivery system for its SBR segment. Moreover, AgI/II is prone to induce T helper type 2 (Th2) responses in mice, such that attempts to use it in a model of delayed-type hypersensitivity that might be amenable to tolerization by mucosal immunization were unsuccessful (M. W. Russell, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Research by Wu and coworkers (Wu et al, 1996(Wu et al, , 1997a has shown that nasal-associated lymphoid tissue (NALT) of intranasal immunized, but not naive, mice contains antigen-specific IgA antibody secreting cells (ASC), indicating that B-cell activation and IgA isotype switching occurs in NALT, with NALT serving as an inductive site for antigenspecific IgA ASC that migrate to distant mucosal effector sites following intranasal immunization. Further research by Wu et al (1996Wu et al ( , 1997aWu et al ( , 1997b has shown that memory T-cells reside in NALT for extended periods, acting in the prevention of the colonization of the nasal cavities. The presence of NALT in the upper respiratory tract, along with the ability to disseminate antigen-specific IgA ASC to distant mucosal effector sites, highlights the importance of NALT in respiratory and oral immunity, and in intranasal immunization (Kuper et al, 1992;Wu et al, 1996Wu et al, , 1997a.…”
Section: Introductionmentioning
confidence: 99%